Viabilidade dos géis a base de quitosana como adjuvantes no tratamento tópico do câncer urotelial de bexiga com imunoterápico: revisão da literatura - Okita, Daniel Takeshi (Universidade Federal de São Carlos, 2024)
Despite recent advances in the areas of prevention and treatment, urothelial bladder cancer remains a challenging condition, holding significant positions in the global ranking of secondary neoplasms. Conventional therapeutic modalities, such as chemotherapy, radiotherapy, and immunotherapy, while widely used, often show limitations in their efficacy. Therefore, there is a need for the development of new localized therapies to enhance efficiency and reduce the adverse effects of treatments. Chitosan gel emerges as a promising adjuvant possibility, exploiting its mucoadhesive properties, ability to enhance bladder permeability, function as a drug delivery system, enable localized treatment, and reduce systemic effects. This work proposes a narrative literature review aimed at determining the potential of chitosan-based gel as an adjuvant in the topical treatment of urothelial bladder cancer. The literature search covered the PubMed, ScienceDirect, and Scielo databases using keywords such as Chitosan, Properties of Chitosan, Treatment of Bladder Cancer, Antitumor Activity of Chitosan, Chitosan Gel in Bladder Cancer. The criteria for selecting articles included those published since 2000, and having explicit terms in their title or abstract related to 'chitosan gel' or experiments involving chitosan gel as an adjuvant in bladder treatment. It was observed that chitosan gel has significant potential as an adjuvant in bladder cancer treatment, with its properties and efficacy demonstrated in the articles highlighting its promising therapeutic application and the possibility of developing new localized therapies
Feasibility of chitosan-based gels as adjuvants in topical treatment of urothelial bladder cancer with immunotherapy: a literature review
Keywords: Imunoterapia; Quitosana; Câncer de bexiga; CIENCIAS BIOLOGICAS::IMUNOLOGIA